Hakim sebagai Pembentuk Hukum dalam Pandangan Pragmatis Realisme bagi Kebebasan Hakim Indonesia dalam Pengambilan Putusan - Mila Karmila Adi (Fakultas Hukum Universitas Islam Indonesia, 1999)
The freedom of lndoriesian Judges in making decision is still asked at this moment. Judge has the duty to maintain justice. He has to have the freedom to do his duty. Yet, the Indonesian Judge is facing some internal and external problems. In thelegal reasoning of Pragmatis Realism believes that the Judicial decision-making is a creative activity, so it needed a qualified thinking from the judge that can be supported by the high technology.Judge is not only ascertain and apply the law also must be makers of law. The legal reasoning of Pragmat is Realismis been hoping to make a good solution thatis related to the freedom of Indonesian Judge.